Optimizing Javanese Script Learning through Thai Script Pedagogy - Rizki Mustikasari; Ratri Harida; Suroto Rosyd Setyanto (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2026)
The declining use of the Javanese script among younger generations has become a major challenge for cultural preservation, while the Thai script (Aksorn Thai) remains widely integrated into Thailand’s educational system despite both scripts sharing the same Abugida writing system. This study aims to conduct a comparative analysis of Javanese and Thai scripts to identify pedagogical strategies that can optimize Javanese script learning. Using a qualitative descriptive method with a comparative approach, data were collected through a literature review, social media content analysis of Thai-language learning, and in-depth interviews with Thai-language experts. The findings indicate that Thai script pedagogy is supported by symbol–word associations, simplified vowel naming, and visual transformation strategies. Accordingly, this study proposes three adaptive strategies for Javanese script instruction: (1) culturally meaningful word associations, (2) simplification of sandhangan terminology into direct phonetic units, and (3) visual approaches to understanding pasangan as transformation patterns. Pedagogically, these strategies encourage more adaptive, visual, and contextualized learning experiences that may enhance students’ motivation, memory retention, and conceptual understanding. The implementation of these approaches is expected to support the revitalization of Javanese script as a living cultural identity in the modern era.